Dynamically induced doublon repulsion in the Fermi-Hubbard model probed by a single-particle density of states - Valmispild, V. N.; Dutreix, C.; Eckstein, Martin; Katsnelson, M.; Lichtenstein, A.; Stepanov, E. A. (Physical Review B, 2020)
We investigate the possibility to control dynamically the interactions between repulsively bound pairs of fermions (doublons) in correlated systems with off-resonant ac fields. We introduce an effective Hamiltonian that describes the physics of doublons up to second order in the high-frequency limit. It unveils that the doublon interaction, which is attractive in equilibrium, can be completely suppressed and then switched to repulsive by varying the power of the ac field. We show that the signature of the dynamical repulsion between doublons can be found in the single-fermion density of states averaged in time. Our results are further supported by nonequilibrium dynamical mean-field theory simulations for the half-filled Fermi-Hubbard model.
CRIS-Team WoS Importer:2020-12-18